2007
DOI: 10.1002/app.26412
|View full text |Cite
|
Sign up to set email alerts
|

Influence of processing conditions on the morphological and mechanical properties of compatibilized PP/LCP blends

Abstract: ABSTRACT:The main aim of this work is to study the influence of the application of different processing conditions on the morphological and mechanical properties of thermoplastic/LCP blends, in which the viscosity ratios are inferior to unity and decrease with increasing temperature. The way the microstructure evolves along the extruder determines the final morphology and thus, the mechanical performance of the systems. In the present case, the mechanical properties are related with the degree of fibrillation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…The formation of fine fibrillar structures and the consequent enhancement in mechanical properties in the direction of flow as has been encountered in our case are highly dependent on the processing conditions employed 28…”
Section: Morphologymentioning
confidence: 54%
See 1 more Smart Citation
“…The formation of fine fibrillar structures and the consequent enhancement in mechanical properties in the direction of flow as has been encountered in our case are highly dependent on the processing conditions employed 28…”
Section: Morphologymentioning
confidence: 54%
“…The formation of fine fibrillar structures and the consequent enhancement in mechanical properties in the direction of flow as has been encountered in our case are highly dependent on the processing conditions employed. 28 The SEM Micrographs (Fig. 8) appear to indicate much more fine and uniform distribution of the LCP fibrils within the PP matrix in presence of compatibilizer in comparison to the PP/LCP blend without any compatibilizer.…”
Section: Scanning Electron Microscopementioning
confidence: 94%
“…The increase of the Young's modulus of our blend with compatibilizer C is also higher than the ones obtained in the past by other researchers with different compatibilizers. 18,30 We must point out, however, that the Young's modulus of blends compatibilized with 4 wt % of compatibilizer E (which is the optimum content of this compatibilizer for our blend, contrary to what happens to the optimum content of compatibilizer C, which is 2 wt %, as we have proved in another work 27 ) becomes slightly higher than the Young modulus of the blend with 2 wt % of compatibilizer C.…”
Section: Discussionmentioning
confidence: 69%
“…In earlier studies, 27,29 we have performed the optimization of the compatibilizer contents for compatibilizers C and E, those that presented (with a 2 wt % compatibilizer content) better mechanical properties. From this study, we concluded that the optimum compatibilizer content for compatibilizers C and E were 2 and 4 wt %, respectively.…”
Section: Mechanical Characterizationmentioning
confidence: 99%
See 1 more Smart Citation